2010
DOI: 10.1097/jgp.0b013e3181d6c0c6
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic and Benzodiazepine Use Among Nursing Home Residents: Findings From the 2004 National Nursing Home Survey

Abstract: Objectives To document the extent and appropriateness of use of antipsychotics and benzodiazepines among nursing home residents using a nationally representative survey. Methods Cross-sectional analysis of the 2004 National Nursing Home Survey. Bivariate and multivariate analyses examined relationships between resident and facility characteristics and antipsychotic and benzodiazepine use by appropriateness classification among residents aged 60 years and older (N = 12,090). Resident diagnoses and information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 28 publications
3
82
1
1
Order By: Relevance
“…In the United States [27], there is a lower use of benzodiazepines due to the safety warnings issued in the late '80 and due to specific actions tackling the high use of these drugs (Medicare part D). Another strength of this study is that our data collection was based on reliable recording from primary sources, namely medication charts and direct clinical information from the treating GP.…”
Section: Strenghts and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States [27], there is a lower use of benzodiazepines due to the safety warnings issued in the late '80 and due to specific actions tackling the high use of these drugs (Medicare part D). Another strength of this study is that our data collection was based on reliable recording from primary sources, namely medication charts and direct clinical information from the treating GP.…”
Section: Strenghts and Limitationsmentioning
confidence: 99%
“…Previous articles indicate the need for documentation of indications to proper evaluate the appropriateness of psychotropic drug use [27,28]. Therefore, the aim of this study was to describe the prevalence of benzodiazepine use in Belgian nursing homes, with attention to indications and dosages for each of the commonly used drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Nationally representative data from 2004 found that 26% of nursing home residents were on an antipsychotic, and that 40% of the prescriptions were inappropriate (Stevenson et al, 2010). Additionally, an innovative, quasi-experimental study compared medication misuse between nursing home and assisted living residents after CMS implemented a series of new regulations in 1999 (Briesacher, Limcangco, Simoni-Wastila, Doshi, & Gurwitz, 2005a).…”
Section: Review Of Obra-87 and Related Interventionsmentioning
confidence: 99%
“…In order to manage NPS among nursing home residents, physicians have commonly prescribed antipsychotics (Briesacher et al, 2005b;Ray, Federspiel, & Schaffner, 1980;Stevenson et al, 2010). Although some data supports their efficacy to manage NPS (Schneider, Dagerman, & Insel, 2006a), antipsychotics are associated with accelerated cognitive decline (Vigen et al, 2011), somnolence, extrapyramidal symptoms, cerebrovascular accidents (Schneider et al, 2006a), and death (Schneider, Dagerman, & Insel, 2005) among older adults with dementia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation